Cancer and Cancer-Related Fatigue and the Interrelationships With Depression, Stress, and Inflammation - Daniel Weber MSc, PhD; Kylie O'Brien PhD (SAGE Publishing, 2017)
Cancer-related fatigue (CRF) is a common symptom experienced in cancer patients. Depression, anxiety, and stress are associated with cancer. Depression and anxiety are also associated with CRF. At the cellular level, much is known about the impact of stress on the body generally, and its potential role in cancer. Stress, anxiety, and depression have been found to depress the immune system. Depression and stress have also been found to create inflammatory changes in the body and there is emerging evidence that inflammation is involved in cancer pathogenesis and in CRF. This article examines the relationships between stress, anxiety, depression, and cancer; relationships between anxiety and depression and CRF; and what happens at the cellular level, including impact on the immune system and emerging evidence of the role of inflammation in CRF. It also reports on research in relation to some Chinese herbal medicines that may be used to treat CRF.